2023
DOI: 10.3390/ijms24098133
|View full text |Cite
|
Sign up to set email alerts
|

AQP3-Dependent PI3K/Akt Modulation in Breast Cancer Cells

Abstract: Aquaporin 3 (AQP3) is a peroxiporin, a membrane protein that channels hydrogen peroxide in addition to water and glycerol. AQP3 expression also correlates with tumor progression and malignancy and is, therefore, a potential target in breast cancer therapy. In addition, epithelial growth factor receptor (EGFR) plays an important role in breast cancer. Therefore, we investigated whether disruption of the lipid raft harboring EGFR could affect AQP3 expression, and conversely, whether AQP3 silencing would affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Next, we examined whether changes in AQP3 expression affected the PI3K/Akt-related signaling pathways, given previous suggestions of AQP3's role in cancer progression through this pathway 27 , 28 . As shown in Figure 3 B, the knockdown of AQP3 in HeLa cells with different concentrations of TGF-β1 reduced the levels of phosphorylated PI3K p85α and Akt, while the total protein expression level was almost unchanged.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we examined whether changes in AQP3 expression affected the PI3K/Akt-related signaling pathways, given previous suggestions of AQP3's role in cancer progression through this pathway 27 , 28 . As shown in Figure 3 B, the knockdown of AQP3 in HeLa cells with different concentrations of TGF-β1 reduced the levels of phosphorylated PI3K p85α and Akt, while the total protein expression level was almost unchanged.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, silencing of AQP3 reduces MMP expression in gastric cancer cells and attenuates invasion and metastasis of gastric cancer cells through a PI3K/Akt-dependent manner 27 . In breast cancer AQP3 has also been shown to regulate oxidative responses and PI3K/Akt activation, affecting its progression 28 , 36 . These studies all support our view that H 2 O 2 acts as a second messenger to promote the progression of cervical cancer through the mediation of AQP3.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR/PI3K and FGFR/ERK signaling pathways play a crucial roles in FGF-2-induced AQP3 expression and contribute to cell migration and metastasis in breast cancer [43]. AQP3-mediated modulation of the PI3K/AKT signaling pathway is specific to different breast cancer cell types [44]. Downregulation of AQP3 reduces proliferation, migration and invasiveness of the MDA-MB-231 TNBC cell line, and enhances the susceptibility of these cells to 5-FU [45].…”
Section: Aqp3mentioning
confidence: 99%
“…This indicates that AQPs may represent novel biomarkers of sepsis [6,11]. However, aquaporin-3 (AQP3) could be of special interest, as it was demonstrated that AQP3 participates in the regulation of pulmonary and intestinal function as well as immune cells in sepsis [6,8,12,13]. AQP3 is a 30 kDa hydrophobic protein and is part of the aquaporin family [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, aquaporin-3 (AQP3) could be of special interest, as it was demonstrated that AQP3 participates in the regulation of pulmonary and intestinal function as well as immune cells in sepsis [6,8,12,13]. AQP3 is a 30 kDa hydrophobic protein and is part of the aquaporin family [12]. AQP3 expression can be found in various parts of the intestine, regulates the proliferation and migration of intestinal epithelial cells, and is responsible for glycerol and hydrogen peroxide transport [13].…”
Section: Introductionmentioning
confidence: 99%